Problem Based Learning Android App Innovation - Adi Ahmad; Fauzan Putraga Al Bahri (IJISTECH (International Journal of Information System and Technology), 2020)
>Nowadays, there are many learning media that have been developed by many programmers either based on mobile or not have became the needs and viewed as a normal situation in education activity. However, there are many learning media in the market that used by many users are still have many problems on it, such as learning media are not able to adjust to the learning problems needed that are facing in higher education. For this reason this research was conducted to create an Android app that applies the concept of Problem Based Learning in order to produce a mobile learning media so that it is expected to be able to improve the achievements of students in schools because it is more effective and efficient.